The making of the black subject: an analysis of the political thought of Anton M. Lembede - Mashile, Nomvuyo (My University, 2020)
This dissertation explores the way in which Anton Lembede analyses the concept of the black subject. Through the lens of the contextual method, it evaluates Lembede’s primary texts in reference to three major themes in his work: (1) the question of Black Poverty, (2) Class and (3) African Nationalism. In the first theme, on the question of black poverty, I argue that Lembede identifies multiple reasons for black poverty and some, but not all of these are rooted in the colonial experience. His reasoning for African destitution is thus complex and interesting. The second theme that Lembede engages with is the question of class. Here, Lembede argues that class as a category should be understood in the context of colonialism but is also a consequence of the predicament of tribalism which is evident in the social structure of black society. Lembede believes that both tribalism and colonial society through its segregationist policies has profoundly contributed towards the undermining of the evolution of the black subject. Third, Lembede provides an account of African Nationalism which he assesses through the lens of religion. Lembede believes that religion is important in so far as establishing a functional concord which promotes the ideals of African Nationalism. He thus analyses the question of the black subject using Christianity as an important tool for the creation of the ideal black subject. Ultimately, I argue that Lembede provides a multilayered perspective on the making of the black subject through a non-secular conceptual analysis. This is because Lembede does not simply equate all black suffering to the colonial malaise but engages with the concept of the black subject in a multi-dimensional approach. Finally, the above ideas have important currency for the manner in which we think about the black subject until the present day because some of these questions have important meaning in present day South Africa
A dissertation submitted in fulfillment of the requirements for the degree of Master of Arts in Political Studies, in the Faculty of Humanities, University of the Witwatersrand, 2020